2001
DOI: 10.1097/00005373-200112000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Preinjury Warfarin Does Not Impact Outcome in Trauma Patients

Abstract: Our data suggest that the PIC of anticoagulation with warfarin does not adversely impact mortality or LOS outcomes in both head and non-head injured patients. In non-head injured patients, however, the occurrence rates and discharge destination were different. More research needs to be done to determine whether this is related to anticoagulation or other reasons (i.e., number of PICs). These data should be used when weighing risk/benefit ratios of prescribing chronic anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 19 publications
1
56
2
1
Order By: Relevance
“…Other investigators have found that head-injured patients on warfarin had a hospital length of stay and mortality rate that were not significantly different from those of matched controls (14).…”
Section: Discussionmentioning
confidence: 86%
“…Other investigators have found that head-injured patients on warfarin had a hospital length of stay and mortality rate that were not significantly different from those of matched controls (14).…”
Section: Discussionmentioning
confidence: 86%
“…22,23 Wojcik et al also found no significant differences between warfarin and the control group with respect to mortality, ICU stay or LOS and discharge disposition. 24 …”
Section: Clopidogrelmentioning
confidence: 99%
“…Le taux de mortalité d'une HIC après traumatisme crânien grave chez un patient sous AVK est de 25 à 50 %, risque vital trois à cinq fois supérieur à celui des HIC post-traumatiques en l'absence de traitement AVK [20][21][22]. Compte tenu de la fréquence des patients chuteurs dans la population gériatrique, il est important de noter que ni l'augmentation de fréquence de survenue d'une HIC sous AVK ni la surmortalité des patients sous AVK ne sont retrouvées quand ne sont pris en compte que les traumatismes crâniens mineurs, sans signe neurologique ni perte de connaissance [23][24][25].…”
Section: éPidémiologie Des Accidents Hémorragiques Des Avkunclassified